A workflow for turbidite reservoir characterization—a case study of the Macedon member, Northern Carnarvon Basin, NW Australia - Song, Yanchen; Yu, Ting; Wang, Youjing; Xiang, Huizhu; Zhang, Yuxiang; Li, Qingshan; Zhang, Yanhong (Frontiers in Earth Science, 2023)
Deep-water turbidite systems on passive continental margins are of interest for oil and gas exploration. However, their complexity poses challenges for reservoir characterization. In this study, we proposed a reservoir characterization workflow for the Macedon member turbidite, employing a combination of 90° phase adjustment, geobody extraction, and genetic inversion, based on the abundant well logging and seismic data from the Enfield field, Northern Carnarvon Basin. Our workflow involved seismic sedimentology to determine the morphology of sand bodies and inversion to determine the net reservoir range, resulting in 3D geological attribute modeling. We applied a 90° phase adjustment correlated seismic events and well logging responses. By stratal slice interpretation and geological body extraction, it was revealed the turbidite reservoir distribution. Finally, we achieved net reservoir characterization of the Macedon member through genetic inversion porosity and geostatistical methods. The results showed that the Macedon turbidite reservoir can be divided into the top and base reservoirs. The top reservoir is sheet-like, and the base reservoir is channelized. The average porosity of the former was 24%, while the average porosity of the later is 20%. The top reservoir has better reservoir quality. Furthermore, we discussed sea level changes affect turbidite distribution and reservoir quality. During the Falling Stage Systems Tract (FSST), the long transportation distance led to relatively less sediment supply and a low sand/mud ratio, resulting in confined, channelized, poor quality turbidite reservoir. In contrast, during the Lowstand Systems Tract (LST), unconfined, amalgamated, good quality turbidite sheet reservoirs were formed. The improved workflow based on seismic sedimentology presented in this article proves effective in characterizing complex reservoirs and contributes to the simplified and efficient management of reservoirs.